Valuable Lessons for Pharmacist PBRNs: Insights and Experiences from Physician PBRN Members - Lourdes G. Planas; Shane P. Desselle; Kaitlyn Cao (MDPI AG, 2019)
Practice-based research networks (PBRNs) rely on a cadre of engaged members to participate in research projects. As pharmacist PBRNs increase in number, it is helpful to understand how members of other professions view their own participation in PBRNs and potential collaborative research endeavors with pharmacists. Due to their longer history of PBRN experience, physician PBRN members may have helpful advice for the establishment of pharmacy networks. The objectives of this study were to describe perceptions among a group of physician PBRN members about: Advice for developing a pharmacist PBRN, practice aspects that might benefit from collaborating with pharmacists who are part of a PBRN, and benefits and challenges of PBRN member participation. This study employed qualitative research methods. Semi-structured interviews were conducted with physician members of the Oklahoma Physicians Resource/Research Network, a primary care PBRN. Advice for establishing a pharmacist PBRN included identifying a champion, recruiting a core group, and conducting a needs assessment. Collaborative areas of interest included medication use management, patient education on chronic disease states, and physician education on new therapies. Participation benefits were categorized as personal satisfaction, improvement in practice quality improvement, advancement of specialty, peer interaction and learning, and real-time information and support. These findings offer insight into strategies for developing and sustaining pharmacist PBRNs and may inform pharmacist PBRN initiatives related to development, member recruitment and retention, and interprofessional project planning with physician PBRNs.